STRATEGI KEPOLISIAN DALAM PENEGAKAN TINDAKAN VANDALISME FASILITAS PUBLIK DI KOTA MAKASSAR PERSPEKTIF SIYASAH SYAR’IYYAH - Majdi, Muhammad Fakhri; Sastrawati, Nila (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
Vandalism is defined as an irresponsible activity of some kind of behavior that tends to be negative. This habit is in the form of scribbling on walls or other objects that can be read by the public. Vandalism refers to the character of someone who destroys other people's property. This behavior is included as a minor crime because it harms other people and really disturbs public comfort. Acts of vandalism in the city of Makassar are not only carried out in public facilities, but also in walls or fences belonging to (private) people. The main problem in this research is how the police strategy to prevent acts of vandalism of public facilities in the city of Makassar perspectivesiyasah syar'iyyah.The type of research used is field qualitative (field reseasch). Based on the results of this study, it shows that acts of vandalism in the city of Makassar, such as graffiti, are often found at several points such as road parapets, shops, direct posts, bus stops, and flyovers. Areas that are prone to acts of vandalism, graffiti, and graffiti are several public places that are busy with people. The forms of doodles made by teenagers also vary, ranging from doodles that are abstract in the form of lines, symbols, initials of letters, initials of numbers, doodles that are in the form of images ranging from pictures of animals, human limbs, landscapes, and murals, doodles in the form of writing. , such as writing that contains elements of ethnicity, religion, race, and inter-group (SARA). Not only that, it is usually associated with ideology, insults, inappropriate jargon.